Peningkatan Perilaku Profesionalisme Pekerja Menghadapi Tantangan Globalisasi pada Abad 21 - Menara Simanjuntak (Binus Business Review, 2010)
The employee professionalism and behavior development are important issues related to their job performance, job satisfaction, and future career. The future of human resource’ needs are determined by the organization’s mission, goal, and strategiy. This research used literature review and other study sources related to the topic using descriptive analysis method. The view study shows that demand for employees are result of demand for the organization’s products or services, more productivities, to reach high performances of revenue and profit. Based on that, management can attempt to establish the number of mix employees needed attempt to reach it. Company’s compensation and benefit program didn’t allow for giving rises to employee who stayed in the same position. The only way for management to reward the top performers was to give them a bonus or promote them to another position. It is more important to adjust the individual professionalism and behavior with the organizational culture and behavior through employee training and course program. The best opportunity for an employee is to catch on job at or to be a manager in another country to get the different experience than their host country as a global attitude. This is a global-oriented view that focuses on using the best approaches.